Pembuatan sistim informasi arsip surat berbasis website (studi kasus : kelurahan sriwidari) - Sally Agustin Elisya; Ivana Lucia Kharisma (Computer Science and Information Technology, 2023)
The rapid development of technology has brought us into a new world, a state where technology takes an important part in everyday life. One that is currently widely used is a website. The development of today's increasingly advanced technology has an impact on the use of technology in people's lives. The development of technology is needed by the community to overcome the problems they face, such as archiving letters or important documents at the village office. Archiving letters or documents at the kelurahan office is related to the archive of incoming and outgoing letters. Letters in the kelurahan office are often damaged or lost, such as being eaten by termites and lost due to fire. There are many incoming and outgoing letters by the Sriwidari Sub-District Office, so that currently we need a system that can help performance related to correspondence. So it is necessary to create a mail archive information system. Mail filing is a record of incoming and outgoing letters received and sent. At this time, the procedures applied to the management of incoming and outgoing letters at the Sriwidari Village Office starting from receiving, making, storing, documenting letters are all done conventionally. With a website-based mail archive information system, it can reduce the difficulty and time spent in the process of searching for mail data, and improve the management of existing mail archiving. This mail archive information system is made using PHP Hypertext Preprocessor (PHP) and MySQL for database processing. The result of this research is to produce an information system that can manage incoming and outgoing mail according to the specified flow, and can solve current problems.